2013
DOI: 10.1289/ehp.1205659
|View full text |Cite
|
Sign up to set email alerts
|

Systems Biology and Birth Defects Prevention: Blockade of the Glucocorticoid Receptor Prevents Arsenic-Induced Birth Defects

Abstract: Background: The biological mechanisms by which environmental metals are associated with birth defects are largely unknown. Systems biology–based approaches may help to identify key pathways that mediate metal-induced birth defects as well as potential targets for prevention.Objectives: First, we applied a novel computational approach to identify a prioritized biological pathway that associates metals with birth defects. Second, in a laboratory setting, we sought to determine whether inhibition of the identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 55 publications
(61 reference statements)
2
19
1
Order By: Relevance
“…Although we observed mostly null associations between arsenic exposures and OFCs, some animal studies reported OFCs (Burk & Beaudoin, 1977;Ferm et al, 1971;Hood et al, 1982;Rogers et al, 1981) and other craniofacial defects (Aggarwal et al, 2007;Ahir et al, 2013) following maternal inorganic arsenic administration during pregnancy. It should be noted that the arsenic doses expected to produce birth defects in animals are likely higher than those typically experienced in human populations, which may account for differences between our results, particularly for drinking water and dietary arsenic exposure, and results from animal studies.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Although we observed mostly null associations between arsenic exposures and OFCs, some animal studies reported OFCs (Burk & Beaudoin, 1977;Ferm et al, 1971;Hood et al, 1982;Rogers et al, 1981) and other craniofacial defects (Aggarwal et al, 2007;Ahir et al, 2013) following maternal inorganic arsenic administration during pregnancy. It should be noted that the arsenic doses expected to produce birth defects in animals are likely higher than those typically experienced in human populations, which may account for differences between our results, particularly for drinking water and dietary arsenic exposure, and results from animal studies.…”
Section: Discussioncontrasting
confidence: 63%
“…Few studies reported OFCs among offspring (Burk & Beaudoin, 1977;Ferm et al, 1971;Hood et al, 1982;Rogers et al, 1981). More recently, two studies examined oral exposures to inorganic arsenic, with one study reporting mid-facial clefts in rats exposed to a combination of an organophosphate pesticide and sodium arsenate (Aggarwal et al, 2007), and the second study reporting craniofacial and neural tube abnormalities in chick embryos exposed to inorganic arsenic at levels under the current Safe Drinking Water Act (SDWA) maximum contaminant level (MCL) for arsenic (Ahir, Sanders, Rager, & Fry, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have identified the GR as a key target for arsenic effects (Ahir et al, 2013; Barr et al, 2009; Bodwell et al, 2004; Gosse et al, 2014; Simons et al, 1990; Stancato et al, 1993). The GR pathway sits at a critical interaction and integration point to play a role in all of the key arsenic associated effects from: inflammation to cognition, and from immunity to neoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…The GR pathway sits at a critical interaction and integration point to play a role in all of the key arsenic associated effects from: inflammation to cognition, and from immunity to neoplasia. Using a comparative toxicogemonics data base, Ahir and colleagues (Ahir et al, 2013) identified the GR pathway as the top affected pathway for arsenic, along with several other thiol reactive metals. The GR pathways were affected by as little as 7.5 ppb arsenic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation